Can we profit from a loss and still expect substantial gains? Grammatical metaphors as discourse builders and translational choices in English and Croatian discourse of economics - Milić Goran; Erdeljić Dubravka Vidaković (ExELL (Explorations in English Language and Linguistics))
The present paper starts from proposed points of synergy between Halliday’s (1998) grammatical metaphors and conceptual metaphors as proposed in Conceptual Metaphor Theory (Ritchie & Zhu, 2015) and concentrates on the nature and function of lexical choices in expert texts on economics in English and their translations in Croatian. The paper identifies and inspects the proposed instantiation types of grammatical metaphor (e.g. nominalizations and transformations to a verb or adjective as instances of transcategorization, taking place not only between lexical items, but also between syntactic categories and through series of transformations. Translational choices and strategies employed in their Croatian translations are then examined to determine the degree of overlap in the adoption and use of grammatical metaphor as both a language possibility and a translation strategy. The choice of translations of economics discourse from English into Croatian aims to test the hypothesis that translations, especially literal ones and those of novel metaphors may introduce new linguistic metaphors in the target language (Samaniego Fernández et al., 2005).